Living Sufism in the Modern World: A Qualitative Textual Analysis of Its Ethical, Social, and Cultural Contributions - Niyaz Ahmad Lone (Research Synergy Foundation, 2026)
This study adopts a qualitative textual analysis and literature-based approach to examine the contemporary relevance of Sufism as a socially engaged ethical tradition. Drawing on classical Sufi texts alongside selected modern scholarly interpretations and case-based discussions, the article analyzes how core Sufi concepts, such as ihsan (spiritual excellence), khidma (service), and mahabba (compassionate love), are articulated and mobilized within present-day socio-cultural contexts. Rather than treating Sufism as an inward or exclusively mystical phenomenon, the study demonstrates how its ethical framework operates in public life through institutional practices, interfaith initiatives, and cultural production. The analysis shows that Sufi traditions contribute to social cohesion by promoting relational ethics grounded in humility and inclusivity, while also providing a counter-discursive resource against exclusivist and polarizing religious narratives. Furthermore, the study highlights how Sufi-inspired cultural forms, particularly devotional literature, music, and ritual performance, function as sites of cultural continuity and adaptive resilience in the face of modern fragmentation. By systematically linking textual principles with contemporary expressions, the article argues that